Exergaming in augmented reality is tailor-made for aerobic training and enjoyment among healthy young adults - Philippe, Antony G.; Goncalves, Aurélie; Korchi, Karim; Deshayes, Maxime (Frontiers in Public Health, 2024)
In recent years, the use of exergaming for physical activity practice has gain in popularity but few is known about the use of augmented reality for physical activity, particularly at moderate to vigorous intensities. The present study examined the use of an exergame in augmented reality for aerobic training in healthy young adults. In a within-subject design, 18 participants (19.8 ± 1.4 years of age) have performed two physical activity sessions playing dodgeball. Indeed, they realized a classical dodgeball session and an exergaming session with an augmented reality version of dodgeball game. Physical loads and intensities were measured with accelerometers, RPE and heart sensors. Enjoyment experienced during the sessions was measured with the short version of the physical activity enjoyment scale questionnaire. Results revealed that both physical load and intensity were appropriate for aerobic training in the two conditions (i.e., classical and exergame in augmented reality) although values were significantly higher in the classical condition. Enjoyment was high in the two conditions with a higher significant value in the classical condition compared to the exergame in augmented reality condition. Put together, these results indicate that an aerobic state can be attained through both physical gameplay and its augmented reality equivalent and was associated to a high level of enjoyment among healthy young adults.